CD4 COUNT FROM CRYOPRESERVATION OF BUFFY COAT AND PBMC - Rasmaya Niruri; Inna Narayani; Wayan Tunas Artama; Mantik Astawa; Ahmad Hamim Sadewa (International Journal of Biosciences and Biotechnology, 2015)
This study aimed to determine CD4 count from cryopreservation of Buffy coat (BC) and PeripheralBlood Mononuclear Cell (PBMC) with and without ficoll. Fifteen EDTA Blood sample (2 ml for eachtube) were drawn from one adult healthy subject. The samples were categorized into five group beforemeasuring the CD4 level (which were fresh whole blood [Group(G)-I], BC without ficoll [fresh <GII>and frozen <G-III>] , and PBMC resulted from BC and ficoll isolation [fresh <G-IV> andfrozen <G-V>]. Each group was replicated three times. Blood storage before preparation was less thanfour hours. Two months cryopreservation using liquid nitrogen (in 40% FBS, 10% DMSO, and RPMI)was conducted. The mean value of CD4 count (cell /mu1) were 522 (G-I), 1410 (G-II), 906 (G-III), 807(G-IV), and 733 (G-V). CD4 count, after 2 month preservation in liquid nitrogen, of the BC sample (G-III) was higher (906 cell /mu1) than PBMC (G-IV) sample (733 cell /mu1).